2020
DOI: 10.4236/fns.2020.114022
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ketogenic-Diet on Health

Abstract: In recent years, the ketogenic diet is the most popular diet around the world. Therefore, keto diet, short for ketogenic, involves eating a high amount of fat, a moderate amount of protein and very few carbs. This research paper aims to know about the effect of a ketogenic diet on our body, to know about the mechanism of the ketogenic diet in treating neurodegenerative disorders and to know about the mechanism of the ketogenic diet in reducing the weight of our body. Also, the objective was to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
0
11
0
3
Order By: Relevance
“…Both fasting and the observation of the ketogenic diet lead to increased oxidation of fatty acids and the use of the ketone bodies produced in that process (β-hydroxybutyrate, acetoacetate and acetone) as the main energy substrate. Therefore, the diet distinguishes itself from other diets since it is not based on energy obtained from glucose but on that from ketone bodies produced from fats [ 8 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both fasting and the observation of the ketogenic diet lead to increased oxidation of fatty acids and the use of the ketone bodies produced in that process (β-hydroxybutyrate, acetoacetate and acetone) as the main energy substrate. Therefore, the diet distinguishes itself from other diets since it is not based on energy obtained from glucose but on that from ketone bodies produced from fats [ 8 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…While, in other diets, the main source of energy is glucose, in this case, the organism preferentially targets ketone bodies. The organism is then put into the so-called nutritional ketosis state, which, in turn, has many favorable applications [ 19 , 20 ]. It is a diet with a low carbohydrate content, high fat content, and moderate protein content.…”
Section: Ketogenic Dietmentioning
confidence: 99%
“…A randomized, double-blind, cross-over pilot study in older adults at risk for AD (11 subjects with and 6 subjects without cognitive impairment) comparing a modified Mediterranean-ketogenic diet (MMKD) with the American heart association diet (AHAD) found that MMKD modulated the gut microbiota and SCFAs associated with AD markers in subjects with mild cognitive impairment [ 160 ]. A ketogenic diet is characterized by high fats, moderate proteins, and very low carbohydrates [ 161 ]. Similarly, in another pilot study, the same group showed that the combination of these two diets (MMKD and AHAD) was able to modulate the gut mycobiome in association with AD markers and uncovered an association between mild cognitive impairment with a fungal–bacterial co-regulation network [ 162 ].…”
Section: Diet and Gut Microbiotamentioning
confidence: 99%